Determinants of Firm Value in Property and Real Estate Firms: Profitability, Liquidity, Firm Size, and Managerial Ownership (2017–2024) - Effendy, Cindy; Rahmah, Nunung Aini; Widianingsih, Indi (Yayasan Az Zukhruf Cendikia, 2026)
Purpose – This study aims to determine the effect of profitability, liquidity, firm size, and managerial ownership on firm value. Design/methodology/approach – This study uses quantitative data, the sample in this study is 15 companies in the property and real estate sector the are listed on the Indonesia Stock Exchange in the period 2017-2024. The analytical technique used to test the hypotheses was multiple regression analysis using Eviews 9 software. Findings – The results of this study show that the profitability variable has a positive and statistically significant effect on firm value, the liquidity variable has a negative and statistically insignificant effect on firm value, the firm size variabel has a negative and statistically significant effect on firm value, and the managerial ownership variabel has a positive and significant effect on firm value. Research limitations/implications – This study discusses firm value and other factors such as profitability, liquidity, firm size, and managerial ownership, focusing on companies in the property and real estate. This study uses Price to Book Value (PBV) as a measure of firm value.